Factors influencing reproductive success in captive populations of Hawaiian Geese Branta sandvicensis - Rave, Elizabeth H; Fleischer, Robert C; Duvall, Fern; Black, Jeffrey M (Wildfowl, 1998)
We determined the effects of inbreeding, husbandry, age, and pair bond tenure on reproductive success in captive populations of endangered Hawaiian Geese, or Nene Branta sandvicensis. We found evidence of inbreeding depressions among captive Nene from Hawaii. At the Hawaiian colony, fertility, hatchability, and total survivorship decreased as male inbreeding coefficient increased, and survivorship decreased as co-ancestry coefficient increased. Husbandry, age and pair bond tenure also influenced reproductive success. At the Hawaiian colony, fertility increased with pair bond tenure, hatchability decreased with incubation type, and total survivorship decreased with incubation type and female age. To maximize reproductive success within the colonies, inbreeding should be minimized, older females should not be allowed to breed, and pari bonds should be maintained.